Antecedents of academic dishonesty among students at selected Malaysian research universities - Ismail, Suriani (2013)
The purpose of this study was to determine the antecedents of academic dishonesty among Malaysian students. In addition, the study was to determine the real scenario of academic dishonesty among higher education students in Malaysia. Two factors with potential for influencing students cheating are identified by a comprehensive review of the literature. The two factors are personal beliefs and values and situational factors. Personal beliefs and values are divided into three dimensions which are idealism, relativism and religious faith. While situational factors are divided into five dimension: opportunity to cheat, peer cheating behavior, acceptance of academic honesty policy, peer disapproval of cheating behavior and perceived severity of penalties for cheating behavior. A set of questionnaires was administered to 3220 tertiary students of four research university (UPM, UKM, UM and USM) who were second year students and above. However, 2606 questionnaires were returned in which 80.9% of response rate. Data collection is by the drop and pick-up method. A pre-test was conducted among 60 UPM students. Data were analyzed using SPSS version 18.0. Descriptive statistics in terms of frequencies, percentages, means and standard deviations were used to describe the scenario of academic dishonesty among higher education students in Malaysia. Pearson product-moment correlation coefficient was used in determining the strength of relationship between independent and dependent variables. This study also used hierarchical multiple regression analysis to examine which factors strongly influence the academic dishonesty by controlling social desirability. Findings revealed that the level of academic dishonesty among tertiary students was low. In addition, the result indicated that plagiarism was the common types of cheating behavior among the students. The analysis of correlation coefficient revealed that personal beliefs and values and situational factors influenced students cheating behavior. Idealism and religious faith negatively influence academic dishonesty. For situationalfactors, peer cheating behavior and opportunity to cheat were positively associated with academic dishonesty. The other two dimensions, acceptance of academic honesty policy and severity of penalties for cheating behavior were negatively associated with academic dishonesty. The result indicated that relativism and peer disapproval behavior are not significantly related to academic dishonesty. The prediction study showed that peer cheating behavior was the strongest contributor to academic dishonesty.